Research co-production in healthcare - Graham, Ian D.; Rycroft-Malone, Jo; Kothari, Anita; McCutcheon, Chris (Hoboken, NJ : Wiley, 2022)
'Research coproduction is an approach to health research that involves working collaboratively with knowledge-users as partners in the research process. It allows multiple perspectives to influence the research question and approach so that it better reflects the needs of those using the knowledge in practice. Decision-making is shared by researchers and knowledge-users throughout the research process. By linking knowledge and practice at the research stage, bilateral or multilateral exchange of expertise leads to more relevant, feasible, and used research findings, and improved dissemination and impact via networks created with the knowledge-users. This introductory chapter defines research coproduction, inclusive of divergent conceptualizations of how stakeholders and knowledge-users are defined and engaged and explores similar collaborative research approaches that have informed the way coproduction is approached and understood. The potential benefits, relevance, and conduct of research coproduction are introduced and sets an initial understanding to explore the various foundations, applications, and processes in the following chapters of this book'--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 06, 2022).
Added to collection customer.56279.3
Keywords: Medicine -- Research; Biology -- Research; Biomedical Research -- methods; Research Design; Intersectoral Collaboration; Biology -- Research; Medicine -- Research